The Participation of FKUB in Maintaining Religious Harmony in Central Mamuju Regency (Dakwah Method Study) - Mattotorang, Muhammad Ilham; Alang, Sattu; Muh. Said, Nurhidayat (Jurnal Mercusuar, 2021)
This research aims to investigate the participation of FKUB in maintaining religious harmony in Mamuju Tengah district. This is a qualitative field research with dakwah, sociological, and juridical approaches. Data collection was done through observation, documentation, and interviews. The results show that the dominant method of dakwah used by FKUB Mamuju Tengah is the al-Hikmah method. This is because the community is diverse in terms of ethnicity, religion, and race. The al-Hikmah method is flexible and can be applied in implementing the mauidzah hasanah and al-Mujadalah methods.